Lived Nation as the History of Experiences and Emotions in Finland, 1800-2000 - Kivimäki, Ville; Suodenjoki, Sami; Vahtikari, Tanja (Palgrave Studies in the History of Experience,, 2021)
This open access book uses Finland in the nineteenth and twentieth centuries as an empirical case in order to study the emergence, shaping and renewal of a nation through histories of experience and emotions. It revolves around the following questions: What kinds of experiences have engendered national mobilization and feelings of national belonging? How have political and societal conflicts turned into new communities of experience and emotion? What kinds of experiences have been integrated into, or excluded from, the national context in different instances? How have people internalized or contested the nation as a context for their personal, family and minority-group experiences? In what ways has the nation entered and affected people's intimate spheres of life? How have "national" experiences been transmitted to children in the renewal of the nation? This edited collection points to the histories of experience and emotions as a novel way of studying nations and nationalism. Building on current debates in nationalism studies, it offers a theoretical framework for analyzing the historical construction of "lived nations," and introduces a number of new methodological approaches to understand the experiences of the nation, extending from the investigation of personal reminiscences and music records to the study of dreams and children's drawings.